2020
DOI: 10.1073/pnas.2002313117
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric deactivation of PIFs and EIN3 by microproteins in light control of plant development

Abstract: Buried seedlings undergo dramatic developmental transitions when they emerge from soil into sunlight. As central transcription factors suppressing light responses, PHYTOCHROME-INTERACTING FACTORs (PIFs) and ETHYLENE-INSENSITIVE 3 (EIN3) actively function in darkness and must be promptly repressed upon light to initiate deetiolation. Microproteins are evolutionarily conserved small single-domain proteins that act as posttranslational regulators in eukaryotes. Although hundreds to thousands of microproteins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“…phyB interacts with both EIN3 and EBF proteins, which facilitates EBF‐targeted EIN3 degradation in a light‐dependent manner (Shi et al, 2016b). Recently, Wu et al (2020) found that PIF transcription factors and EIN3 can form functional oligomers by self‐interaction. Two microproteins, miP1a and miP1b, interact with and disrupt the self‐association and oligomerization of PIFs and EIN3, suppressing the DNA‐binding ability and the transcriptional activity of PIFs and EIN3 (Wu et al, 2020).…”
Section: Ein3/eil1‐mediated Transcriptional Activation Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…phyB interacts with both EIN3 and EBF proteins, which facilitates EBF‐targeted EIN3 degradation in a light‐dependent manner (Shi et al, 2016b). Recently, Wu et al (2020) found that PIF transcription factors and EIN3 can form functional oligomers by self‐interaction. Two microproteins, miP1a and miP1b, interact with and disrupt the self‐association and oligomerization of PIFs and EIN3, suppressing the DNA‐binding ability and the transcriptional activity of PIFs and EIN3 (Wu et al, 2020).…”
Section: Ein3/eil1‐mediated Transcriptional Activation Cascadementioning
confidence: 99%
“…Recently, Wu et al (2020) found that PIF transcription factors and EIN3 can form functional oligomers by self‐interaction. Two microproteins, miP1a and miP1b, interact with and disrupt the self‐association and oligomerization of PIFs and EIN3, suppressing the DNA‐binding ability and the transcriptional activity of PIFs and EIN3 (Wu et al, 2020). Interestingly, protein degradation regulation has been found to occur in nearly every step of the canonical ethylene signaling pathway.…”
Section: Ein3/eil1‐mediated Transcriptional Activation Cascadementioning
confidence: 99%
“…Increasing studies have revealed that individual BBX protein has different functions. BBX4 and BBX21-BBX23 are positive regulators for light signaling, whereas BBX19, BBX24, BBX25 and BBX28-BBX32 inhibit photomorphogenesis [ 20 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Some BBXs form a transcriptional regulatory network with ELOGATED HYPOCOTYL 5 (HY5) through affecting HY5 activity to regulate photomorphogenic development.…”
Section: Pif4-interacting Transcriptional Regulatorsmentioning
confidence: 99%
“…Another interesting example of a BBX protein involved in regulation of hypocotyl growth is BBX31/microprotein 1a (miP1a), which can either promote or repress photomorphogenesis depending on the light context: BBX31 inhibits photomorphogenesis induced by R, FR, or B in hypocotyls, while it promotes UV‐B‐mediated growth repression (Heng et al ., 2019; Yadav et al ., 2019). It is possible that BBX31 inhibits hypocotyl growth in response to UV‐B by binding to PIFs and inhibiting their oligomerization (Wu et al ., 2020). Specifically, it has been demonstrated that BBX31, as well as its close homolog BBX30/miP1b, can interact with PIF3 and reduce its assembly into tetramers, thus inhibiting the ability of this PIF to activate the expression of genes such as PIL1 (Wu et al ., 2020).…”
Section: Repression Of Hypocotyl and Petiole Growth By Lightmentioning
confidence: 99%
“…It is possible that BBX31 inhibits hypocotyl growth in response to UV‐B by binding to PIFs and inhibiting their oligomerization (Wu et al ., 2020). Specifically, it has been demonstrated that BBX31, as well as its close homolog BBX30/miP1b, can interact with PIF3 and reduce its assembly into tetramers, thus inhibiting the ability of this PIF to activate the expression of genes such as PIL1 (Wu et al ., 2020). Notably, another BBX protein, BBX4, also binds PIF3 and inhibits its ability to activate target gene expression, which explains its negative effect on hypocotyl growth in R (Datta et al ., 2006; Heng et al ., 2020).…”
Section: Repression Of Hypocotyl and Petiole Growth By Lightmentioning
confidence: 99%